An overview of Centella asiatica and its therapeutic applications - Aszrin, Farashakira Najiah; Adam, Siti Hajar; Abdul Mutalib, Maisarah; Tang, Hooi Chia; Tang, Shirley Gee Hoon (Life Sciences, Medicine and Biomedicine, 2024)
Globally, medicinal herb intervention has become popular in treating many illnesses. Centella asiatica (C. asiatica), a plant native to Southeast Asia, is utilized extensively due to its pharmacological and therapeutic benefits attributed by its triterpenoids and saponins. It has been widely researched for a variety of medicinal properties, including antidiabetic, antioxidant, wound healing, reproductive, sedative, anxiolytic, digestive, gastric ulcer, cognitive, antidepressant, and anti-inflammatory effects. The sedative qualities are associated with regulating the HPA axis to mitigate stress and modulate GABAergic activity, while its capacity to promote collagen production, provide antioxidant protection, and lower inflammation aids in the healing of wounds. Owing to a wide range of literature on C. asiatica, the significant discoveries about various diseases are occasionally overlooked. Hence, more concise and succinct information is warranted. This review aimed to summarize the potential medicinal aspects of C. asiatica, highlighting the medicinal properties, physicochemical properties and health benefits along with future direction of the therapeutic potential. While many of the well-established properties and effects have been proven, the procurement of further clinical trials must be attended to involving the determination of standardized procedures and investigate the ultimate possible function of C. asiatica in treating diverse medical diseases, thus, to fully comprehend the therapeutic benefits of the herb. By possessing numerous pharmacological properties, C. asiatica could potentially offer greater assistance in the medical world for treating the patients while minimizing risks and mitigating degenerative effects.